Portuguese Validation of the Dissociative Experiences Scale (DES) - Espirito-Santo, Helena (2013)
Objective: The Dissociative Experiences Scale (DES) is a widely used screening tool for dissociative symptoms. The aim of the present study was to evaluate the validity and internal consistency of a Portuguese version and determine if it accurately identified dissociative pathology. Method: The original DES underwent a “forward–backward” translation process. The translated form was used on 570 participants divided into 3 subgroups: 113 patients with dissociative symptoms, 233 psychiatric patients with vari- ous psychopathological disorders, and 224 normal individuals. Results: A principal components analysis with all of the partici- pants yielded 4 factors that accounted for 56.3% of the variance. Reliability as measured by Cronbach’s alpha was .94. The receiver operating characteristic curve applied to the cutoff analysis revealed a value of 30 comparing the 2 clinical groups and con- trasting the dissociative-based group with the nonclinical group. The ability of the DES to correctly classify those with and without the disease was very good. Sensitivity was 65.0% and specificity was 86.0% with the cutoff score of 30 from the comparison between dissociative symptomatic disorders and the other psychopathological disorders. Comparing the dissociative symptomatic group with the nonclinical group, we found that sensitivity was 65.0% and specificity was 100%. The mean DES scores for the 3 subgroups were significantly different. Conclusion: These findings are in some degree analogous to those in other studies and suggest that the DES is a reliable and valid screen for the Portuguese population.